Pragmatic posterior capsular stretch and its effects on shoulder joint range of motion - Keramat Ullah Keramat; Muhammad Naveed Babur (BMJ Open Sport & Exercise Medicine, 2020)
Objective To evaluate the immediate effects of pragmatic posterior capsular stretch (PPCS) on shoulder joint range of motion (ROM).Method A quasi-experimental design was used to recruit healthy subjects of age 21.43 (±1.960) years, height 165.8 (±2.1069) cm and weight 63.90 (±13.187) kg. Inclusion criteria were grade 1 and grade 2 of the shoulder mobility test of functional movement screening. Preintervention and postintervention measurement of flexion, abduction, internal rotation (IR), external rotation (ER), reaching up behind the back (RUBTB) and reaching down behind the neck (RDBTN) were compared. A therapist-administered PPCS was the only intervention applied.Results Paired t-test statistics showed improvement (mean°±SD) in shoulder flexion (13.5°±8.11), abduction (11°±8.35), IR (8.5°±10.27), ER (7.83°±7.15), RUBTB (17.34°±13.81) inches and RDBTN (2.93±1.52) inches. The changes in these ROM and functional movements were statistically significant (p<0.05).Conclusion PPCS can effectively improve the functional movement of RUBTB and shoulder ROM in healthy subjects. It is recommended for the trials on prevention and rehabilitation of shoulder pathologies.Trial registration number NCT04242888.